Tvorac i delo - Čakić, Miroslav Ž. (Stylistyka, 2021)
WorkIn this paper we have posited the basie thesis that a created work of art depends exclusive- ly on its creator, namely on his worldview, his experience of the world. Two authors are discussed here, the poets V. Petković Dis and A. Śantić, who belonged to the same literary movement, the same literary school, and should therefore have used similar, if not the same forms of expression. Moreover, the two poets wrote on the same topie, the topie of autumn, had the same audience - and should have treated the identical topie in a similar way according to the same poetics. However, notwithstanding the same elements: the same poetical movement (modemism), the same topie (autumn), the same audience (the beginning of the 2Oth century), the two poets created two works of art (two poems) com- pletely different in form, and in content too. This has confirmed that within the well-known triad: who —> for whom —> what, the who element plays the dominant part, as the naturę of what depends on it, even though the for whom element is identical in different cases. This is a proof of Buffon’s well-known statement - the style is the man, namely that the form and content of a created work of art solely depends on the creator, writer.